Effect of ozone or carbon dioxide pre-treatment during long-term storage of organic table grapes with modified atmosphere packaging. (December 2018) - Admane, Naouel; Genovese, Francesco; Altieri, Giuseppe; Tauriello, Antonella; Trani, Antonio; Gambacorta, Giuseppe; Verrastro, Vincenzo; Di Renzo, Giovanni Carlo
Abstract: The aim of this study was to maintain the quality of organic table grapes extending its shelf-life during long-term storage by using organic approved methods. The effectiveness of pre-treatments with different concentrations of O3 (5, 10, 20 μL L −1 ) or CO2 (50%, 70%) followed by storage under modified atmosphere packaging (2%O2 5%CO2 ) were evaluated on late-season organic Scarlotta table grapes as alternatives to the usual commercial SO2 application. The main quality attributes as mass loss, decay incidence, rachis chlorophyll content, antioxidant activity, phenolic compounds and acetaldehyde content, were measured at harvest and after 15, 30, 45 days of cold storage (0 °C) under simulated shipping conditions and one week of shelf-life (15 °C). The O3 at 20 μL L −1 controlled the concentration of acetaldehyde, preserved rachis chlorophyll content and skin colour; in addition, the cumulative decay incidence was reduced compared to untreated samples, however, CO2 caused organoleptic quality loss with strong stem browning and perceived off-flavours; moreover, it was effective to preserve the initial sensory quality and to control the decay. The results encourage the use of this alternative approach treatment in other cultivars and under commercial conditions. Highlights: O3, CO2 pre-treatments could be used in long term storage of organic table grapes. O3 pre-treatment allowed decay control by maintaining EU commercial standards. Pre-treatments with O3, CO2 and MAP are an alternative to SO2 for table grapes.